Loops and spurs: the angular power spectrum of the Galactic synchrotron background - Mertsch, P; Sarkar, S (IOP Publishing, 2013)
We present a new model of the diffuse Galactic synchrotron radiation, concentrating on its angular anisotropies. While previous studies have focussed on either the variation of the emissivity on large (∼ kpc) scales, or on fluctuations due to MHD turbulence in the interstellar medium, we unify these approaches to match the angular power spectrum. We note that the usual turbulence cascade calculation ignores spatial correlations at the injection scale (∼ 100 pc) due to compression of the interstellar medium by of O(1000) old supernova remnants - the 'radio loops' only four of which are visible in radio maps. This new component naturally provides the otherwise missing power on intermediate and small scales in the all-sky map at 408 MHz. Our model can enable more reliable subtraction of the synchrotron foreground for studies of CMB anisotropies or searches for dark matter annihilation. We conclude with some remarks on the relevance to modelling of the polarised foreground.